2018 IEEE Integrated STEM Education Conference (ISEC) 2018
DOI: 10.1109/isecon.2018.8340471
|View full text |Cite
|
Sign up to set email alerts
|

Novel approach for cybersecurity workforce development: A course in secure design

Abstract: Training the future cybersecurity workforce to respond to emerging threats requires introduction of novel educational interventions into the cybersecurity curriculum. To be effective, these interventions have to incorporate trending knowledge from cybersecurity and other related domains while allowing for experiential learning through hands-on experimentation. To date, the traditional interdisciplinary approach for cybersecurity training has infused political science, law, economics or linguistics knowledge in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In addition to the above-mentioned recommendations, the railway workforce can also use the following literature such as:National Centers of Academic Excellence in Cyber Defense (CAE-CD) program (CAE, 2020)Security Education and Training Awareness (SETA) program (CDSE, 2020)A Guide to the National Initiative for Cybersecurity Education (NICE) cybersecurity workforce framework (Shoemaker et al , 2018)The future cybersecurity workforce (Dawson and Thomson, 2018)Cybersecurity workforce development for the nation (Dill, 2018)A novel approach for cybersecurity workforce development (Sharevski et al , 2018)A Strategy for a cybersecurity culture (Gcaza and Von Solms, 2017)A peer mentoring approach toward cybersecurity workforce development (Janeja et al , 2016)Cybersecurity workforce development and the protection of critical infrastructure (Chapman, 2017)…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above-mentioned recommendations, the railway workforce can also use the following literature such as:National Centers of Academic Excellence in Cyber Defense (CAE-CD) program (CAE, 2020)Security Education and Training Awareness (SETA) program (CDSE, 2020)A Guide to the National Initiative for Cybersecurity Education (NICE) cybersecurity workforce framework (Shoemaker et al , 2018)The future cybersecurity workforce (Dawson and Thomson, 2018)Cybersecurity workforce development for the nation (Dill, 2018)A novel approach for cybersecurity workforce development (Sharevski et al , 2018)A Strategy for a cybersecurity culture (Gcaza and Von Solms, 2017)A peer mentoring approach toward cybersecurity workforce development (Janeja et al , 2016)Cybersecurity workforce development and the protection of critical infrastructure (Chapman, 2017)…”
Section: Discussionmentioning
confidence: 99%
“…While scholars still highlight the need for technical training to keep pace with changes (e.g., [3], [8]) there is also recognition that the fundamentals of security are not technical but human [9] - [12]. In addition, [7. p. 10] observed that "although today's cybercrime is worlds apart from the hacking of the 1980's…the fundamental techniques…have not changed."…”
Section: B Present Calls For Changementioning
confidence: 99%
“…Different Teaching Methods (Zeng et al, 2018;Yuan, 2017;Qian et al, 2012;Thompson & Irvine, 2018;Sharevski et al, 2018;Katerattanakul & Kam, 2019;Mislan & Wedge, 2016;Straub, 2018;Ahmed & Roussev, 2018;Govan, 2016;Jin et al, 2018;Zahed et al, 2019;Gestwicki & Stumbaugh, 2015;Olano et al, 2014;Li & Kulkarni, 2016) • To offer different methods of teaching cybersecurity in addition to the traditional methods to spark interest in newcomers and enhance training for current students.…”
Section: Initiatives To Attract Cybersecurity Studentsmentioning
confidence: 99%
“…In their study,Mislan & Wedge (2016) proposed a similar ideology for their cybersecurity and digital forensics labs. They designed a lab environment that allowed students to assume roles and interact with each other while handling smallscale digital devices Sharevski et al (2018). sought to include students from other disciplines in cybersecurity related topics.…”
mentioning
confidence: 99%